2001
DOI: 10.1046/j.1442-2018.2001.00080.x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of nurses' intention to administer opioids for pain relief

Abstract: A statewide cross-sectional survey was conducted in Australia to identify the determinants of registered nurses' intention to administer opioids to patients with pain. Attitudes, subjective norms and perceived control, the key determinants of the Theory of Planned Behavior, were found to independently predict nurses' intention to administer opioids to these patients. Perceived control was the strongest predictor. Nurses reported positive overall attitudes towards opioids and their use in pain management. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
51
2
7

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 33 publications
5
51
2
7
Order By: Relevance
“…1,27 Results from the present study are in line with previous reports on morphinophobia among health professionals by Broekmans et al 28 and Edwards et al 22 Several studies demonstrate that a good knowledge of pain mechanisms and the certitude of pharmacological efficacy favorably influence attitudes toward the use of morphine. 22,28,29 However, knowledge alone is rather insufficient to guarantee its application, nor to induce a knowledge-based behavior. Attitudes related to behavior develop over a long time period and are linked to a social context.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…1,27 Results from the present study are in line with previous reports on morphinophobia among health professionals by Broekmans et al 28 and Edwards et al 22 Several studies demonstrate that a good knowledge of pain mechanisms and the certitude of pharmacological efficacy favorably influence attitudes toward the use of morphine. 22,28,29 However, knowledge alone is rather insufficient to guarantee its application, nor to induce a knowledge-based behavior. Attitudes related to behavior develop over a long time period and are linked to a social context.…”
Section: Discussionsupporting
confidence: 92%
“…21 This is also true when it comes to use and administration of opioids to patients. 22 The theory of reasoned 23 action serves as theoretical framework in this study. According to the Ajzen and Fishbein theory of reasoned action, 23,24 the adoption of a behavior by an individual is the immediate result of the behavioral intention.…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…Surprisingly, Wells (2001) found that improving knowledge regarding opioids via training in pain management was not effective in improving attitudes towards use of opioids. Many nurses were still uncomfortable administering opioids for pain relief, including for breakthrough pain (Edwards et al, 2001). On the other hand, Edwards (2001) found that a supportive environment promoted better attitudes towards administering breakthrough opioids.…”
Section: Introductionmentioning
confidence: 99%
“…Many nurses were still uncomfortable administering opioids for pain relief, including for breakthrough pain (Edwards et al, 2001). On the other hand, Edwards (2001) found that a supportive environment promoted better attitudes towards administering breakthrough opioids.…”
Section: Introductionmentioning
confidence: 99%
“…These factors (time management, shift worked, impact of members of the multidisciplinary team, concerns over opioid analgesics, and communication) are consistent with the findings of other authors who have suggested that the culture of the care environment significantly influences pain management. [13][14][15][16][17][18][19][20][21][22] In the time since Willson's 2000 study, 13 acute pain management in orthopedic surgery has undergone a revolution. In particular, the emergence of peripheral nerve blocks for postoperative analgesia has resulted in improved pain scores, reduced opioid requirements, and improved mobility in TKA.…”
Section: Introductionmentioning
confidence: 99%